The Effectiveness of Using Picture Book to Motivate Students Especially Young Learners in Reading - Putu Santi Oktarina; Ni Putu Lila Sri Hari; Ni Made Winda Ambarwati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This journal aims to investigate the effectiveness of PICTUREBOOK in resolve the problem of low interest in reading, especially for young learners. Reading is something that is learned. Reading means gaining an understanding of the written symbols represented by the sounds of oral language. This is an important skill to learn as it opens the doors to further studying, better job opportunities and to a whole other world that happens in print. There are many strategies that can be used to teach reading for young learners one of them is by using a picture book. A picture book is a book contained illustrations on each page accompanied by texts which tell about the same story told by the illustrations. In this journal, the authors use a qualitative research method, by reviewing some journals from other researchers. The result of this research proves that picture books can improve and motivate young learners to enhance and also motivate young learners to prefer reading. Picture books can visualization literacy skills and train children to comprehend the story from multiple perspectives.